2011
DOI: 10.1124/jpet.111.181636
|View full text |Cite
|
Sign up to set email alerts
|

Transient Lower Esophageal Sphincter Relaxation Pharmacokinetic-Pharmacodynamic Modeling: Count Model and Repeated Time-To-Event Model

Abstract: Transient lower esophageal sphincter relaxation (TLESR) is the major mechanism for gastroesophageal reflux. Characterizations of candidate compounds for reduction of TLESRs are traditionally done through summary exposure and response measures and would benefit from model-based analyses of exposure-TLESR events relationships. Pharmacokinetic (PK)-pharmacodynamic (PD) modeling approaches treating TLESRs either as count data or repeated time-to-event (RTTE) data were developed and compared in terms of their abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…First, the evaluation of a binary covariate that changes over time should be performed. Then, we should also study the impact of a continuous covariate changing or not over time (30).…”
Section: Discussionmentioning
confidence: 99%
“…First, the evaluation of a binary covariate that changes over time should be performed. Then, we should also study the impact of a continuous covariate changing or not over time (30).…”
Section: Discussionmentioning
confidence: 99%
“…Daily vomit frequencies over 8 days were evaluated using a Poisson model, as previously described (19,20). The suitability of the Poisson model was evaluated by plotting the individual mean frequency against variance to evaluate for equidispersion.…”
Section: Genotypingmentioning
confidence: 99%
“…Compared with traditional plasma based assays, 7 these whole blood based assays provide a more detailed description of the global haemostasis function which includes the cellular components of haemostasis. 13 These are important components that may affect clinical efficacy and need to be accounted for. Previous in vitro 8 and ex vivo 9 studies have reported that TEG allowed for individualization of treatment regimens of rhFVIIa and pd-aPCC in haemophilia patients with inhibitors.…”
Section: Introductionmentioning
confidence: 99%